The Influence of Motivation and Work Environment on Employee Performance: At a Fashion Company in Bandung - Ikhsan, Muhamad Nurul; Machmud, Senen; Manik, Ester; Danasasmita, Windi Matsuko (Center of Research, STIE Pasundan, Bandung, Indonesia., 2024)
This study aims to analyze the impact of motivation and work environment on employee performance. It employs Descriptive and Verification Methods. The data source utilized in this study consists of a questionnaire administered to employees of a fashion firm located in Bandung. The research has a sample size of 35 respondents. The research employs Descriptive and Verification Methods as its statistical methodologies. The initial step involves employing Correlation Data Analysis, Path Analysis, and Coefficient of Determination Analysis, with assistance from the SPSS (Statistical Product and Service Solution) program version 26. After conducting a comprehensive study of the data collected, the Motivation, Work Environment, and Employee Performance at a fashion company in Bandung are categorized as somewhat reasonable. The R Square number indicates that it is 75.5%. Employee Performance is primarily influenced by Motivation and Work Environment, accounting for 75.5% of the overall impact. The remaining 24.5% is attributed to unexplored factors. In addition, Motivation has a lesser impact, accounting for 42.3% of the total influence, in contrast to the Work Environment, which has a total influence of 50.6%. Companies should prioritize creating a conducive work atmosphere while striving to optimize Motivation in a fashion company in Bandung.